Environmental approach to geographic thinking development from the perspective of José Marti’s texts - González Sivilla , Roeris; Montero López , Maritza; Miranda Rangel , Raúl (Transformación, 2024)
The article presents findings of the research the project "Systematization of the theory and practice for a didactics of geographical thinking in natural sciences teacher currently running at the Faculty of Sciences. The study is intended to highlight the potentials of José Marti’s text for environmentally focused geographical thinking junior high school students. It starts by assessing the importance of geographical thinking for contemporary society and the presence of this conception in the writings and the life of José Martí, Eighth grade Geography objectives and content suitable for José Marti’s studies are identified. Likewise, a selection of texts is suggested.